2010
DOI: 10.1111/j.1574-6976.2010.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing membrane stress: the phage shock protein (Psp) response, from molecular mechanisms to physiology

Abstract: The bacterial phage shock protein (Psp) response functions to help cells manage the impacts of agents impairing cell membrane function. The system has relevance to biotechnology and to medicine. Originally discovered in Escherichia coli, Psp proteins and homologues are found in Gram-positive and Gram-negative bacteria, in archaea and in plants. Study of the E. coli and Yersinia enterocolitica Psp systems provides insights into how membrane-associated sensory Psp proteins might perceive membrane stress, signal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
270
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(279 citation statements)
references
References 200 publications
(559 reference statements)
8
270
0
1
Order By: Relevance
“…In addition, a great deal of data have recently indicated that, besides their contribution to the repair mechanisms after stress exposure, there is a direct involvement of several HSPs in the modulation of cell proliferation and apoptosis, which is confirmed by the fact that almost all human tumors display a specific combined alteration of different HSPs (in particular HSP70, HSP90, and HSP27) (33,34). Hence, HSPs have become potential therapeutic targets and their quantification could become a putative diagnostic marker (35)(36)(37)(38). In this report, three major and closely correlated findings are reported, namely (i) IDE expression is stress-inducible in malignant and not-malignant cells; (ii) IDE concentration is in vivo markedly up-regulated in some tumors of the central nervous system; (iii) IDE down-regulation impairs SHSY5Y cell proliferation and viability, being accompanied by a decrease in the overall content of poly-ubiquitinated proteins, likely reflecting an influence of IDE on the ubiquitin-proteasome system.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, a great deal of data have recently indicated that, besides their contribution to the repair mechanisms after stress exposure, there is a direct involvement of several HSPs in the modulation of cell proliferation and apoptosis, which is confirmed by the fact that almost all human tumors display a specific combined alteration of different HSPs (in particular HSP70, HSP90, and HSP27) (33,34). Hence, HSPs have become potential therapeutic targets and their quantification could become a putative diagnostic marker (35)(36)(37)(38). In this report, three major and closely correlated findings are reported, namely (i) IDE expression is stress-inducible in malignant and not-malignant cells; (ii) IDE concentration is in vivo markedly up-regulated in some tumors of the central nervous system; (iii) IDE down-regulation impairs SHSY5Y cell proliferation and viability, being accompanied by a decrease in the overall content of poly-ubiquitinated proteins, likely reflecting an influence of IDE on the ubiquitin-proteasome system.…”
Section: Discussionmentioning
confidence: 90%
“…In this sense, it has been reported that monomeric Ub degradation by IDE appears inhibited by nestin, a type VI intermediate filament protein expressed by many cell types during development and at high levels by tumor cells, such as neuroblastoma and glioma cells (9,37).…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] One potent and highly specific activator of the Psp response is the mislocalization of pore forming "secretin" proteins into the inner membrane. 29,30 The Psp response is thought to react to, and mitigate, specific events that compromise the integrity of the inner membrane.…”
Section: Introduction To Gram-negative Esrsmentioning
confidence: 99%
“…2C, middle panel). PspA is a peripheral IM-associated stress protein that responds to impaired membrane function (26,52). Although the biological function of PspA is far from clear, it appears to play a role in the maintenance of the PMF upon cell envelope stress.…”
Section: Resultsmentioning
confidence: 99%